Mapping of Land Use Shifting in Tourism Area of Lake Toba, Indonesia. (August 2019) - Sinaga, I N; Sejati, A W; Muktiali, M; Rahayu, S
Abstract: Lake Toba has become a priority destination since it was designated as a National Tourism Strategic Tourism (KSPN) one of which is the village of Tomok. This study aims to analyze the influence of Lake Toba as a National Tourism Strategic Area on changes in land use and the economy of the local community of Tomok Village using GIS modeling. This research uses quantitative descriptive method with descriptive statistical analysis, before-after analysis and interpretation of satellite imagery. The results of this study are that the Lake Toba program as KSPN affects the economy of the local community of Tomok Village. Society experiences changes in income levels, shifts in basic work and the creation of basic and side jobs. Changes in the highest level of income occurred in hotel / lodging businesses, which previously amounted to 4, 000, 000- 6, 500, 000 IDR, which increased to 10, 000, 000 IDR. Then, there was a shift in the main work in the agricultural business sector to become the hotel manager and souvenir trader, the souvenir trader became the owner of an inn and the grocery store owner became a souvenir trader. In addition, there is the creation of basic jobs and side jobs. People who previously did not have a basic job became hotel employees as many as 5 people and food stall owners as many as 3 people. In shifting side jobs, the dominant community that previously did not have side jobs. After 2014, the local community chose to work side by side to increase income. Side jobs that arise are farmers, restaurant owners and souvenir traders. Then land use changes that occur are not significant but the change in the function of buildings from residential to commercial buildings is very large. The land that has changed is the transfer of Tomok Ferry Port to empty land which is now the center of trade and services.